2022
DOI: 10.1186/s12916-022-02530-x
|View full text |Cite
|
Sign up to set email alerts
|

Proactive community case management decreased malaria prevalence in rural Madagascar: results from a cluster randomized trial

Abstract: Background Malaria remains a leading cause of morbidity and mortality worldwide, with progress in malaria control stalling in recent years. Proactive community case management (pro-CCM) has been shown to increase access to diagnosis and treatment and reduce malaria burden. However, lack of experimental evidence may hinder the wider adoption of this intervention. We conducted a cluster randomized community intervention trial to assess the efficacy of pro-CCM at decreasing malaria prevalence in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In our trial, age-expanded mCCM resulted in an immediate and sustained uptake of this intervention by individuals of all ages, resulting in over 85,000 RDTs done and 60,000 ACT treatments provided for individuals older than 5 years of age at the community level during the 14-month implementation period, equivalent to 1.2 additional RDTs done by CHWs per workday. Overall, annual rates per capita roughly tripled in the intervention arm for RDTs done (from 0.41 to 1.16) and for ACTs given (from 0.21 to 0.77), an increase comparable to that observed in a recent study of proactive (home-based) malaria CCM in south-eastern Madagascar [ 16 ]. Survey results revealed that CHW diagnosis and treatment of older ages for fever was already taking place before the intervention started, and this practice increased in the control arm following implementation (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our trial, age-expanded mCCM resulted in an immediate and sustained uptake of this intervention by individuals of all ages, resulting in over 85,000 RDTs done and 60,000 ACT treatments provided for individuals older than 5 years of age at the community level during the 14-month implementation period, equivalent to 1.2 additional RDTs done by CHWs per workday. Overall, annual rates per capita roughly tripled in the intervention arm for RDTs done (from 0.41 to 1.16) and for ACTs given (from 0.21 to 0.77), an increase comparable to that observed in a recent study of proactive (home-based) malaria CCM in south-eastern Madagascar [ 16 ]. Survey results revealed that CHW diagnosis and treatment of older ages for fever was already taking place before the intervention started, and this practice increased in the control arm following implementation (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…This is already the case in many countries pursuing malaria elimination nationally or sub-nationally [ 12 ]. In moderate to high transmission settings, engaging CHWs in efforts to visit homes at regular intervals, identify febrile household members, and test and treat them according to a standard protocol, a strategy known as proactive community case management (pro-CCM), has shown some success in increasing malaria cases detected [ 13 , 14 ] and improving malaria outcomes [ 15 , 16 ]. However, pro-CCM approaches can be time- and resource-consuming for CHWs, who are often volunteers in many SSA countries due in part to a lack of funding for community health programs.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of seasonality, higher prevalence was estimated for December to May from re-analyses of health facility data ( 76, 77 ), with a peak around April ( 78 ). Few recent epidemiological studies with active sampling are available from the region, but prevalence among households (all ages) varied from 3-46% by locality in 2017 from cross-sectional prevalence surveys ( 44, 79 ).…”
Section: Methodsmentioning
confidence: 99%
“…CHW programs provide basic maternal and child care within local communities of several hundred to several thousand people (Perry 2020). CHWs traditionally diagnose and treat malaria in children under 5 years of age, and recent pilot programs have demonstrated the success of expanding responsibilities to include novel malaria interventions, such as the provision of intermittent preventive treatment to pregnant women (Pons-Duran et al 2021) or proactive screening and treatment (Ratovoson et al 2022). These successes of community-targeted programs have prompted calls for the increased development of digital health tools for programs implemented at local scales, especially in sub-Saharan Africa (Holst et al 2020, Owoyemi et al 2022).…”
Section: Introductionmentioning
confidence: 99%